Estimation of cascading hydroclimatic hazard impacts on supply systems and associated economic shocks - Marlon Vieira Passos; Jung-Ching Kan; Georgia Destouni; Karina Barquet; Luigia Brandimarte; Zahra Kalantari (npj Natural Hazards)
Abstract Emerging systemic risks driven by climate extremes and societal vulnerabilities are causing considerable damage to supply systems and overall economies. In this study, we combined hydroclimatic hazard impact and supply-driven input-output models to develop an integrated approach for estimating the cascading impacts on food, electricity, and water supply associated with droughts, floods, and heatwaves. National-level results for Sweden indicate moderate to strong associations between annual supply variables and monthly climate indices (0.39 ≤ R 2 ≤ 0.62) at municipal units. Economic modeling revealed losses in key sectors, such as agriculture, energy, and insurance. The results from this economic modeling show that combined hydroclimatic hazards between 2005 and 2022 inflicted €8.4 billion of economic damage on agriculture, electricity, and insurance. Of this, flood-related damage represented the largest share, totaling €4.1 billion, followed by drought-induced supply shortages (€2.9 billion), and heatwave impacts (€2.3 billion).